2015
DOI: 10.1519/jsc.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate–Based Training Intensity and Its Impact on Injury Incidence Among Elite-Level Professional Soccer Players

Abstract: an increase in training volume at high intensity levels were related to injury incidence, or 6 increased the odds of injury. Training intensity was assessed through time spent in two high-7 and very high-intensity zones of 85-<90% and ≥90% of maximal heart rate (T-HI and T-VHI, 8 respectively), and all injuries were recorded over two consecutive seasons. Twenty-three elite 9 professional male soccer players (meanSD age 25.64.6 years, stature 181.86.8 cm, and 10 body mass of 79.38.1 kg) were studied through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 32 publications
7
58
0
6
Order By: Relevance
“…Other specific measurement types identified by teams included rating of perceived exertion (RPE) heart rate (HR) and GPS. Although not currently shown in elite football players, workloads from training and matches as measured using RPE17–21 were associated with injury in other elite team sports, while early, albeit limited, studies in elite footballers have shown a link between injury and workload as measured using HR22 and GPS 23. Until research further validates (or refutes) these workload variables in professional football, the current limited and, in some cases, extrapolated evidence may provide an insight into how elite football teams might be able to interpret their workload data as calculated from RPE, HR and GPS; specifically, these aforementioned studies have shown that high cumulated loads and acute spikes/increases in load for players may provide pertinent information.…”
Section: Discussionmentioning
confidence: 92%
“…Other specific measurement types identified by teams included rating of perceived exertion (RPE) heart rate (HR) and GPS. Although not currently shown in elite football players, workloads from training and matches as measured using RPE17–21 were associated with injury in other elite team sports, while early, albeit limited, studies in elite footballers have shown a link between injury and workload as measured using HR22 and GPS 23. Until research further validates (or refutes) these workload variables in professional football, the current limited and, in some cases, extrapolated evidence may provide an insight into how elite football teams might be able to interpret their workload data as calculated from RPE, HR and GPS; specifically, these aforementioned studies have shown that high cumulated loads and acute spikes/increases in load for players may provide pertinent information.…”
Section: Discussionmentioning
confidence: 92%
“…High absolute training and/or competition load was identified as a risk factor for injury in athletics/running,86–107 baseball,42 108–110 cricket,111–116 football (soccer),117 118 orienteering,119 rugby league,120–125 rugby union,126 127 swimming,106 128 triathlon,129–134 volleyball135 and water polo 136. On the other hand, high absolute load was reported as not increasing injury risk in different studies that included athletics/running, Australian football, rugby league, rugby union and triathlon 137–151.…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 99%
“…Although there has been some inconsistency between the results of different studies on load and injuries in the different football codes, most studies seem to indicate that high loads are associated with an increased injury rate (table 5). In football, players who participate in more high intensity training, defined as time spent with a heart rate of 85-90% of their maximal heart rate, have been found to be more likely to sustain an injury [94].…”
Section: Load and Injuries In The Football Codesmentioning
confidence: 99%